2003
DOI: 10.1016/s0248-4900(03)00035-2
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic release factors (eRFs) history

Abstract: In the present review, we describe the history of the identification of the eukaryotic translation termination factors eRF1 and eRF3. As in the case of several proteins involved in general and essential processes in all cells (e.g., DNA replication, gene expression regulation...) the strategies and methodologies used to identify these release factors were first established in prokaryotes. The genetic investigations in Saccharomyces cerevisiae have made a major contribution in the field. A large amount of data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
83
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(88 citation statements)
references
References 148 publications
2
83
0
2
Order By: Relevance
“…Sup35, which can convert into the [PSI + ] prion, is normally a GTPase subunit of the translational termination factor responsible for the release of nascent protein chains from the ribosome (reviewed in ref. 14). Het-S/[Het-s] is a determinant for heterokaryon incompatibility (reviewed in ref.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%
“…Sup35, which can convert into the [PSI + ] prion, is normally a GTPase subunit of the translational termination factor responsible for the release of nascent protein chains from the ribosome (reviewed in ref. 14). Het-S/[Het-s] is a determinant for heterokaryon incompatibility (reviewed in ref.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 97%
“…A previous report suggested that ϩ1 frameshifting might occur at a stop codon in eRF1-depleted cells (32). To address this possibility, a frameshift construct harboring a reporter in which different epitopes were positioned to distinguish between frameshifting at the PRF versus at the stop codon.…”
Section: ϫ1 Frameshifting Does Not Occur At a Stop Codon Proximal To mentioning
confidence: 99%
“…Eukaryotic release factor 1 (eRF1) was originally identified in a screen in the yeast Saccharomyces cerevisiae and was identified as a suppressor of nonsense mutations and designated SUP45 (32). Subsequent genetic and biochemical analyses demonstrated that SUP45 was a translational release factor which then also became known as eRF1 (32).…”
mentioning
confidence: 99%
See 2 more Smart Citations